Creative teacher’s products: Identifying innovation in physical education learning - Sri Wicahyani; Suroto Suroto; Vega Candra Dinata; Gema Fitriady; Febri Wasono Aji; Sigit Ansori; Ghulam Zaky Ismail; Bobby Ade Setiawan; Rizky Prayuda Putra (Universitas Ahmad Dahlan, 2025)
This study aims to identify innovations in physical education (PE) learning carried out by teachers. This study is a systematic review on the Google Scholar database. We set inclusion criteria, namely articles published in the last 5 years, the author is a teacher, and the searching keyword for the article is ‘innovation in physical education learning’. Therefore, any article wriiten by non-PE teachers was excluded, as it can be seen from the authors’ affiliation. The results of the study refer to the analysis of 13 articles that match the criteria, indicating that teachers have made innovations in physical education learning. The innovations include learning media, models, and methods. The Innovations were carried out to improve students’ learning outcomes in the cognitive, affective, and psychomotor domains, as well as to increase the students’ learning motivation. The learning environment designed by the teacher will affect the learning process and student learning outcomes. Finally, we suggest PE teachers to continuously make innovations, not only to improve learning outcomes, but also to provide memorable learning experiences at every meeting.